Construction and Engineering Application of Salt-Discharging Model for Local Saline-Alkali Soil with Compact Structure in the Yellow River Delta - Chuanxiao Liu; Kesheng Li; Depeng Ma (Applied and Environmental Soil Science)
Structural characteristics of local saline-alkali soil in the Yellow River Delta were studied by microscopic test methods of liquid nitrogen vacuum freeze-drying machine, fully automatic mercury intrusion porosimetry, X-ray diffractometer, and high- and low-vacuum scanning electron microscope. Permeability of the saline-alkali soil belongs to two grades of micropermeable water and extremely micropermeable water. Average volume ratio of pores with diameters no more than 2 μm is 86.25%; therefore, the saline-alkali soil may mainly consist of micropores and ultramicropores. Most void ratios of the soil are not beyond 0.5, and its dry densities are all greater than 1.6 g/cm3. Because average proportion of the clay minerals is only 12.24%, they are obviously not the main reason for poor permeability of the local saline-alkali soil. Based on the structural characteristics of compact structure and slightly developed fracture, mechanisms of surface runoff, and water-salt migration of the local saline-alkali soil, a salt-discharging engineering model mainly with surface runoff was established considering auxiliary infiltration and without interflow. Salt content distribution of the local saline-alkali soil is studied experimentally, by which relationship between salt content and conductivity has been fitted as y = 2.74x. The relationships between depth and salt content in the saline-alkali soil region present that the depth of salt-discharging engineering as open ditch should be beyond 60 cm. From the relationships between precipitation and salt content, the effectiveness of engineering measure shown in the salt-discharging model has been verified immediately or indirectly, and the engineering salt-discharging model may be suitable for managing saline-alkali soil in the Yellow River Delta.